EFFECT OF SiO2 AND ZnO NANOPARTICLES TO INCREASE REFRIGERATION MACHINE PERFORMANCE - Dandi Irwansyah; Rita Sundari; Rini Anggraini; Khuzaimah Arifin (Universitas Mercu Buana, 2023)
In this investigation, the impact of silicon dioxide (SiO2) and zinc oxide (ZnO) nanoparticles on the performance of a refrigeration machine system was systematically examined. The focus was on evaluating the coefficient of performance (COP) concerning the utilization of a polyolester (POE) lubricant, R600a refrigerant, and distinct nanoparticles (SiO2 and ZnO) within the refrigeration system. The nanoparticles were individually introduced into the R600a refrigerant in masses of 0.5 g, 1.0 g, and 1.5 g. The experimental outcomes demonstrated a noteworthy enhancement in COP with the addition of nanoparticles. Specifically, the introduction of 1.5 g of SiO2 resulted in a substantial increase of 25.88% in COP, marking it as the most influential dosage. Similarly, the addition of 1.0 g of ZnO led to a significant COP increase of 13.6%, representing the optimal quantity for ZnO. Furthermore, the inclusion of 1.5 g of SiO2 brought about a remarkable reduction in energy consumption, with a decrease of 25.58%, while 1.5 g of ZnO resulted in a notable 16.28% decrease in energy consumption. The experimental configuration involved the use of 20 g of refrigerant and 500 ml of POE lubricant. Comparative analysis demonstrated that the refrigeration system incorporating nanoparticles outperformed the conventional R600a refrigeration system devoid of nanoparticles. This study contributes valuable insights into the potential enhancements in refrigeration system efficiency through the strategic incorporation of SiO2 and ZnO nanoparticles, offering a promising avenue for optimizing the performance of refrigeration technology.